The design process in teacher development for the evaluation of digital educational material in school setting (Research, Society and Development, 2019)
This study aims to analyze the design process in continued teacher development to encourage the evaluation of digital educational material. The methodology used in the study was Design-Based Research (DBR) from three stages: diagnosis, intervention and analysis. The results of the combined stages point to design principles, which can contribute to establish a design for teacher development. Hence, they also suggest that the evaluation of digital educational material conducted by teachers can be a "core point" in the development process.